Integrating geospatial technologies into the right-of-way data-management process - Hancock, Kathleen L. (Research results digest (National Cooperative Highway Research Program), 2006)
"This digest presents the key findings from NCHRP Project 8-55, "Integrating Geospatial Technologies into the Right-of-Way Data-Management Process," conducted by Kathleen L. Hancock , Center for Geospatial Information Technology, Virginia Polytechnic Institute and State University, Alexandria, Virginia"--P. [1].